Career History Archival Medical and Personnel System. - Gunderson EKE; Garland CF; Miller MR; Gorham ED; Gunderson, E K Eric; Garland, Cedric F; Miller, Milan R; Gorham, Edward D (Military Medicine, 2005)
The Career History Archival Medical and Personnel System is a database that provides information on cancer, chronic diseases, occupational and preventive medicine, epidemiological research, and the use of health care in the Navy and Marine Corps. It was created at the Naval Health Research Center for enlisted Navy personnel, and it is being expanded to encompass all military personnel. Its objective is to provide a comprehensive, chronologically ordered database of career and medical events in all active duty military service members and to track career and disease events in order from the date of entry to service to the date service ended. Events include the dates of beginning and ending of each specific military occupation, all assignments to a military units or ships, all hospitalized diseases, and other events. The database contains detailed epidemiological data on more than six million members of the military services. It is the largest known epidemiological database in the United States.